Dekonstruksi Narasi Pancasila dalam Pendidikan Moral: Tantangan dan Strategi di Era Post-Truth - Kurnianto, Benny; Abdusshomad, Alwazir; Kalbuana, Nawang (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to describe the challenges of implementing the values of Pancasila in moral education in the post-truth era, a time when the flow of disinformation and information polarization is rapidly growing and influencing the mindset of the younger generation. This study employs a literature review method by gathering data from various sources such as scientific journals, books, and relevant articles. The analysis technique used is content analysis, which allows researchers to systematically and deeply elucidate the meaning of the texts. The analysis shows that the values of Pancasila need to be conveyed through a more dialogical, reflective, and adaptive approach to the social dynamics that occur. In this case, teachers play an important role as critical learning facilitators that encourage students' active involvement in understanding and internalising these values. Participatory learning allows students to develop critical thinking skills, media literacy, and stronger national awareness. This research concludes that strengthening students' national identity and moral character in the post-truth era relies heavily on pedagogical innovations that are rooted in Pancasila values but responsive to the challenges of the times